Willingness of the Senior High School Teachers to be Vaccinated against COVID-19 - Markhipolito Galingana; Angelito Alvarado; Donna Lamug Reyes; Ericka Perpose; Jamaica Pasion; Analyn Rigos; Marife Solito (Humanistic Network for Science and Technology (HNST), 2021)
The SARS-Coronavirus 2019 (COVID-19) pandemic is a major threat to public health and has a significant impact on all aspects of life. An effective vaccine is the most anticipated solution for controlling the spread of the COVID-19 virus and reducing this disease's cases. The study aims to determine the willingness of public senior high school teachers to the COVID-19 vaccine. The researchers conducted a study on the willingness of the public senior high school teachers on April 2021 submitted to the faculty of the College of Nursing of Isabela State University (Echague, Main Campus). The researchers used a descriptive research design method, convenient sampling technique, and adopted a tool for the data gathering of the study. The findings indicated that although most respondents are willing to be vaccinated with Pfizer BioNTech COVID-19 vaccine, some refused; the primary reasons for rejection are the vaccine's side effects and efficacy. The study results suggest that the participants have a high acceptance level of the COVID 19-vaccine. The researchers recommend government agencies responsible for the COVID-19 vaccine campaign to take into consideration the findings of this study regarding the reasons of refusal of the respondents for the improvement of the campaign about COVID-19 vaccine. Keywords: COVID-19 vaccine; vaccination program; willingness to be vaccinated